Pharmacological Properties of Ginsenoside Re - Gao, Xiao-Yan; Liu, Guan-Cheng; Zhang, Jian-Xiu; Wang, Ling-He; Xu, Chang; Yan, Zi-An; Wang, Ao; Su, Yi-Fei; Lee, Jung-Joon; Piao, Guang-Chun; Yuan, Hai-Dan (Frontiers in Pharmacology, 2022)
Ginsenoside Re is a protopanaxatriol-type saponin extracted from berry, leaf, stem, flower bud and root of Panax ginseng. It has been attracting attention as a dietary phytochemical in recent years. Studies on ginsenoside Re (Re) were compiled by searching a combination of keywords, namely including “pharmacology”, “pharmacokinetics” and “toxicology” in the main databases, namely PubMed, Google Scholar, Web of Science and NCBI. The aim of this review was to provide a exhaustive overview and extensive overview of the pharmacological activities, pharmacokinetics, and toxicity of Ginsenoside Re, focusing on the clinical evidences which have shown particular effectiveness in specific diseases, such as diabetes mellitus (DM), nervous system disease,inflammation, cardiovascular disease, and cancer. Re is also known to eliminate virus, enhance immune response, improve osteoporosis, improve skin barrier function, enhance intracellular anti-oxidant, regulate cholesterol metabolism, alleviate allergic response, increase sperm motility, restore erectile dysfunction, promote cyclic growth of hair follicles, and reduce gastrointestinal motility dysfunction. Furthermore, this review also provided data on pharmacokinetic parameters and toxicological factors to support the favorable safety profile of Re. These data can provide a theoretical basis and reference for Re-related studies and its application in the future.